(3GdTGYQ (B/s - (3GdefadhWj , eUWai dWaj s; (3bGSe, QjGVs ((3HjQhJ (B:s (3eDSSI HMShf (B:s (3OGQ GdefGd,s, 2001)
(3eDda gPg GdQhGjI GdcGJH GdaQfSj EOehf QhSJGf(B. (3JMcj SjQI TGYQ hHWd YGTb, hbO LYdgG GdefadhWj QhGjI eMhdG EjGgG ef GdbGdH GdJeKjdj Edi GdbGdH GdbUUj(B.s
(3eDda gPg GdQhGjI GdcGJH GdaQfSj GOehf QhSJGf hbO GYJfi GdefadhWj YfGjI cHjQI HUjGZI gPg GdQhGjI aLGAJ HMb eJjfI GdSHc hQbjbI GdJYHjQ hObjbI GdCOGA bhjI GdJCKjQ hZfjI GdCSdhH s
Keywords: (3QhSJGf , GOehfs -- 1619-1655 -- (3QhGjI s -- (3aQfSG s; (3GdbUU GdaQfSjIs